Creatine deficiency syndrome caused by guanidinoacetate methyltransferase deficiency: Diagnostic tools for a new inborn error of metabolism - Schulze, Andreas; Heß, Thomas; Wevers, Ron; Mayatepek, Ertan; Bachert, Peter; Marescau, Bart; Knopp, Michael V.; De Deyn, Peter Paul; Bremer, Hans J.; Rating, Dietz (The journal of pediatrics, 1997)
Hepatic guanidinoacetate methyltransferase deficiency induces a deficiency of creatine/phosphocreatine in muscle and brain and an accumulation of guanidinoacetic acid (GAA), the precursor of creatine. We describe a patient with this defect, a 4-year-old girl with a dystonic-dyskinetic syndrome in addition to developmental delay and therapy-resistant epilepsy. Several methods were used in the diagnosis of the disease: (1) the creatinine excretion in 24-hour urine was significantly lowered, whereas the creatinine concentration in plasma and in randomly collected urine was not strikingly different from control values; (2) the Sakaguchi staining reaction of guanidino compounds in random urine samples indicated an enhanced GAA excretion; (3) GAA excretion measured quantitatively by guanidino compound analysis using an amino acid analyzer was markedly elevated in random urine samples; (4) in vivo 1H magnetic resonance spectroscopy (MRS) revealed a strong depletion of creatine and an accumulation of GAA in brain; (5) in vivo phosphorus 31 MRS showed a strong decrease of the phosphocreatine resonance and a resonance identified as guanidinoacetate phosphate; and (6) in vitro 1H MRS showed an absence of creatine and creatinine resonances in cerebrospinal fluid and the occurrence of GAA in urine. For early detection of this disease, we recommend the Sakaguchi staining reaction of urine from patients with dystonic-dyskinetic syndrome, seizures, and psychomotor retardation. Positive results should result in further investigations including quantitative guanidino compound analysis and both in vivo and in vitro MRS. Although epilepsy was not affected by orally administered creatine (400 to 500 mg/kg per day), this treatment resulted in clinical improvement and an increase of creatine in cerebrospinal fluid and brain tissue. (J Pediatr 1997;131:626-31)
Elektronische Reproduktion der Druck-Ausgabe 2. November 2005
Gesehen am 20.06.2024